Genetically modified organisms, grade 7 STEM road map for middle school - Johnson, Carla C., 1969-; Walton, Janet B., 1968-; Peters-Burton, Erin E. (New York, NY : Routledge, 2022)
What if you could challenge your seventh graders to become informed citizens by analyzing real-world implications of GMOs? With this volume in the STEM Road Map Curriculum Series, you can! Genetically Modified Organisms outlines a journey that will steer your students toward authentic problem solving while grounding them in integrated STEM disciplines. Like the other volumes in the series, this book is designed to meet the growing need to infuse real-world learning into K-12 classrooms. This interdisciplinary, five-lesson module uses project- and problem-based learning to help students investigate the opportunities and challenges of GMO production and consumption. Working in teams, students will create a documentary communicating the health, social, and economic aspects of GMO production and consumption. To support this goal, students will do the following: Use the Internet and other sources to build knowledge of an issue, and recognize and value stakeholders and their viewpoints in an issue. Explore the relationship among local, state, and federal legislation related to GMOs. Understand the role of cost-benefit analysis in making informed economic decisions. Develop skills to evaluate arguments, create and communicate individual understanding and perspectives. Gain a deeper understanding that structure and function are related by examining plants and how the environment and genetics influences structure. Gain a better understanding of what tools humans have developed to genetically alter organisms for human benefit. The STEM Road Map Curriculum Series is anchored in the Next Generation Science Standards, the Common Core State Standards, and the Framework for 21st Century Learning. In-depth and flexible, Genetically Modified Organisms can be used as a whole unit or in part to meet the needs of districts, schools, and teachers who are charting a course toward an integrated STEM approach.
Keywords: Transgenic organisms -- Study and teaching (Middle school); Genetic engineering -- Study and teaching (Middle school); EDUCATION / Teaching Methods & Materials / Science & Technology; EDUCATION / Teaching Methods & Materials / Mathematics; EDUCATION / Curricula